Recalibrating the breakup history of SW Gondwana: the first U-Pb chronostratigraphy for the Uitenhage Group, South Africa - Muir, Robert Anthony (Department of Geological Sciences, 2019)
Syn-rift deposits often provide the only means to determine the processes for initiation and evolution of rift basins and passive margins. The structurally preserved erosional remnants of several rift basins that formed during the Mesozoic breakup of Gondwana are located within the southern Cape region of South Africa. These onshore basins contain the Suurberg and Uitenhage Groups, which are predominantly continental, taphrogenic, fossiliferous strata interbedded with volcaniclastics. Their significance in the Gondwanan breakup events is poorly understood due to a lack of precise and accurate radioisotopic ages. The development of SW Gondwana into the modern passive margins of southern Africa, South America and Antarctica, as well as the evolution of life recorded in the regional strata are difficult to evaluate without a high resolution chronostratigraphic framework. By integrating field observations with U-Pb geochronology of over 4000 detrital and primary volcanic zircons from pyroclastic, mixed-origin volcaniclastic and sedimentary rocks by Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICPMS), this thesis presents the first radioisotopic ages for the Uitenhage Group and provides a new chronostratigraphic framework for the onshore Jurassic – Cretaceous in the southern Cape. To further improve precision and accuracy, a selection of crystals from four pyroclastic deposits in key stratigraphic positions were selected for single-zircon Chemical Abrasion – Thermal Ionisation Mass Spectrometry (CA-TIMS) analysis to minimize the effects of Pb-loss and constrain depositional age uncertainties to < 1%. These new age constraints show that the Suurberg Group was deposited rapidly during the emplacement of the Karoo and Ferrar Large Igneous Province in the Early Jurassic (Pliensbachian) and likely predates the main phase of rifting in the southern Cape, whereas the Uitenhage Group was deposited over a prolonged (> 40 Ma) period from the Early Jurassic into the Early Cretaceous and records two phases of rifting: an initial Jurassic episode that roughly coincides with the separation of East and West Gondwna and is contemporaneous with widespread volcanism in SW Gondwana; and a subsequent period of renewed rifting during the Early Cretaceous opening of the South Atlantic. Trace element geochemical and zircon morphological assessments indicate that the volcanic source that supplied ash into the growing rift basins in the southern Cape during Gondwana breakup was situated in modern-day Patagonia and the Antarctic Peninsula, which were proximal to the southern Cape in the Jurassic and Early Cretaceous. The valuable geological framework presented in this dissertation illustrates the complexity of long-lived, rift-basin sedimentation and highlights the importance of high-resolution chronostratigraphy when investigating the tectonic, palaeontological and palaeogeographical records from the final moments of a unified Gondwana.